The Impact of Mergers and Acquisitions on Shareholders' Welfare - Susanto, Jeffrey Belmiro; Tirtamurti, Lim Madeleine; Reynard, Dave; Linawati, Nanik (FKIP Universitas Lampung, 2024)
The objective of this research is to analyse mergers and acquisitions (M&A) in Indonesia the period 2017 - 2021. This study examines the determinants of abnormal returns of acquirer companies which consist of: Return on Assets, return on equity, Total Asset turnover, Fixed asset turnover, and Gross Profit Margin. This research examines 42 merger and acquisition events during 2017 - 2021. The research data was processed using multiple regression. The results of the research reveals that 5 factors that were used including return on assets, return on equity, total asset turnover, fixed asset turnover, and gross profit margin did not significantly affect the abnormal return of the acquisition company.Keywords: Abnormal return, Financial performance, Mergers and AcquisitionDOI: http://dx.doi.org/10.23960/E3J/v7i1.7-12